Toxoplasma Chinese 1 Strain of WH3Δrop16I/III/gra15II Genetic Background Contributes to Abnormal Pregnant Outcomes in Murine Model - Wang, Cong; Cheng, Weisheng; Yu, Qian; Xing, Tian; Chen, Shoubin; Liu, Lei; Yu, Li; Du, Jian; Luo, Qingli; Shen, Jilong; Xu, Yuanhong (Frontiers in Immunology, 2018)
Toxoplasma gondii infection evokes a strong Th1-type response with IL-12 and IFN-γ secretion. Recent studies suggest that the infection of pregnant mice with T. gondii may lead to adverse pregnancy results caused by subversion of physiological immune tolerance at maternofetal interface rather than direct invasion of the parasite. Genotype-associated dense granule protein GRA15 II tends to induce classically activated macrophage (M1) differentiation and subsequently activating NK, Th1 and Th17 cells whereas rhoptry protein ROP16I/III drives macrophages to alternatively activated macrophage (M2) polarization and elicits Th2 immune response. Unlike the archetypal strains of types I, II and III, type Chinese 1 strains possess both GRA15II and ROP16I/III, suggesting a distinct pathogenesis of Toxoplasma-involved adverse pregnancies. We constructed T. gondii type Chinese 1 strain of WH3Δrop16 based on CRISPR/Cas9 technology to explore the ROP16I/III deficient/GRA15II dominant parasites in induction of trophoblast apoptosis in vitro and abnormal pregnant outcomes of mice in vivo. Our study showed that Toxoplasma WH3Δrop16 remarkably induced apoptosis of trophoblasts. C57BL/6 pregnant mice injected with the tachyzoites of WH3Δrop16 presented increased absorptivity of fetuses in comparison with the mice infected with WH3 wild type (WH3 WT) parasites although no remarkable difference of virulence to mice was seen between the two strains. Additionally, the mice inoculated with WH3Δrop16 tachyzoites exhibited a notable expression of both IL-17A and IFN-γ while the percentage of CD4+CD25+FoxP3 (Tregs) were diminished in splenocytes and placenta tissues compared to those infected with WH3 WT parasites. Accordingly, expressions of IL-4, IL-10 and TGF-β1, the pivotal cytokines of Th2 and Tregs response, were significantly dampened whereas IFN-γ and IL-12 expressions were upregulated in WH3Δrop16 infected mice, which gave rise to more prominent outcomes of abnormal pregnancies. Our results indicated that the WH3Δrop16 parasites with gra15II background of T. gondii type Chinese 1 strains may cause miscarriage and stillbirth due to subversion of the maternal immune tolerance and system immunity of the animals and the GRA15II effector contributes to the process of adverse pregnant consequences.